Exploring Effective Interventions for Postpartum Blues: A Systematic Literature Review - Ika Novita Sari; bin Sansuwito, Tukimin (Holistic Nursing Plus, 2025)
This literature review explores interventions for postpartum blues, a condition that affects up to 80% of new mothers. A systematic analysis was conducted on research published between 2010 and 2024, sourced from PubMed, CINAHL, and PsycINFO databases. Of the 1,247 initial articles, 72 met the inclusion criteria following a comprehensive screening process. The findings indicate that psychosocial interventions, particularly peer support and cognitive-behavioral therapy (CBT), provide the most substantial evidence for effectiveness. Additionally, emerging approaches, including hormonal treatments, nutritional supplementation, and technology-based support, show promising potential. The review also highlights the need for standardized outcome measures, longer-term studies, and culturally adapted interventions. The results advocate for implementing personalized, multimodal approaches and integrating these interventions into routine perinatal care. This review makes a significant contribution to evidence-based practices aimed at supporting maternal mental health during the critical postpartum period.